Introduction to dossier. The production of the social sciences in Latin America - Kingman Garcés, Eduardo; Hurtado, Edison (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2008)
Introduction to dossier. The production of the social sciences in Latin America